Production of Konjac Glucomannan Antimicrobial Film for Extending Shelf Life of Fresh-Cut Vegetables - Panya Saeheng; Panuwat Eamsakulrat; Orachorn Mekkerdchoo; Chaleeda Borompichaichartkul (My University, 2016)
The aim of this research was to produce konjac glucomannan (KGM) antimicrobial film with added sweet basil oil (SB) (Ocimum basilicum) as an antimicrobial agent for inhibiting coliform bacteria which is the type most often found in fresh-cut vegetables. The concentrations of SB oil in the emulsion that inhibited the most antimicrobial growth were 4% and 6% (v/v). Film-forming conditions were evaluated by varying the volume of KGM solution per area (0.325, 0.455 and 0.585 mL·cm−2) and the concentration of SB oil (4% and 6%). After mixing the film emulsions, the emulsions were dried on a tray dryer at 50 °C for 10 h. After drying, the results showed that KGM film made at 0.325 mL·cm−2 with SB oil at 4% resulted in the smoothest surface. When the film was tested against Escherichia coli, KGM at 0.325 mL·cm−2 with 4% SB oil and at 455 mL·cm−2 with 6% SB oil produced the greatest inhibition. Film with SB oil at 4% was used to study film properties. Physical properties of the film such as tensile strength (68.08 MPa) and % elongation (33.56%) as well as water vapor transmission rate (4.44 × 10−3 g·cm−2·h−1) were determined. The KGM/SB film did not show an antimicrobial effect on packages of fresh-cut baby cos lettuce or spring onion under the experimental conditions. Further work will be carried out to study more closely the controlled release properties of KGM/SB film to enhance its antimicrobial effects. These improvements could help to develop a more successful application for its use as a natural biopreservative in minimally-processed products like fresh-cut vegetables.
Keywords: Elongation; Nanocomposite Films for Food Packaging